PENGARUH HARGA, PROMOSI, DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN IM PARFUME DI TOKO DEENA BEAUTY KOTA BATAM - Baene, Nuruati; Hendriati, Yossi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2023)
The research aims to determine the effect of price, promotion and service on purchasing decisions for Im parfume at the Deena beauty store in Batam City. In this study, a quantitative method was used in which data were obtained from survey results and questionnaire data processing based on statistical procedures. Based on the Lemeshow formula, the sample in this study is 100 respondents. In this study, the results of the Y regression equation were 11.008 + 0.276X1 + 0.016X2 + 0.127X3 + e. The price variable has an influence on purchasing decisions with a tcount value (2.443) > ttable (1.984), promotion variable has no efect on purchasing decisions with tcount (0.146) < ttable (1.984), service variable has no influence on purchasing decisions with tcount value (1.358) < ttable (1.984), and the variables of price, promotion and service have an effect simultaneously by showing the results of the calculation of Fcount (5.128) > Ftable (2.70) where if Fcount > Ftable. While the R2 value is 0.1986 or 13.8% which indicates that the independent variables (X1, X2, X3) affect the dependent variable (Y) by 13.8%, while the remaining 86.2% is influenced by other variables outside this study.